Upregulated expression of vascular endothelial growth factor in proliferative diabetic retinopathy. Issue 3 (March 1996) - Pe'er, J; Folberg, R; Itin, A; Gnessin, H; Hemo, I; Keshet, E
Abstract : AIMS/BACKGROUND: Vascular endothelial growth factor (VEGF) is a hypoxia induced angiogenic factor. Recent studies have shown that high levels of VEGF accumulate in the vitreous of patients with proliferative diabetic retinopathy (PDR). The purpose of the present study was to identify the retinal cells that upregulate VEGF expression in human PDR patients representing progressive stages of retina deterioration. METHODS: Thirteen formalin fixed and paraffin embedded enucleated eyes with PDR were used (eyes were enucleated because of being blind and painful as a result of neovascular glaucoma). Thin retina sections were hybridised in situ with a VEGF specific probe, to identify cells producing VEGF mRNA. RESULTS: All eyes with PDR showed upregulated expression of VEGF mRNA, specifically in the cells of the neurosensory retina. VEGF expression was upregulated in all three nuclear layers--namely, the ganglion cell layer, the inner nuclear layer, and the outer nuclear layer. However, in each patient, VEGF producing cells were mostly distributed in a different layer, or even confined to a specific region in that layer. For example, expression by the outer nuclear layer was mostly detected in detached (presumably hypoxic) regions of the retina. CONCLUSIONS: Progression of PDR is distinguished by a sustained, upregulated expression of VEGF by the neurosensory retina. Cells in all retina layers can potentially contribute to augmented VEGF production. The restricted population of VEGF producing cells in each case is likely to represent cells residing in ischaemic regions of the retina. Thus, VEGF may function as a linking factor between retinal ischaemia and PDR associated neovascularisation.